On Being a First-Year Student: A Hidden Perspective in the Design Studio (EAAE Annual Conference Proceedings, 2019)
This research provides an important opportunity to advance our understanding of the evolving conception of learning in the design studio and specifically how first year students at architecture schools adapt to their new learning environment.
Keywords: student’s experience; first-year experience; reflections